1987
DOI: 10.7326/0003-4819-106-1-1
|View full text |Cite
|
Sign up to set email alerts
|

Oral Norfloxacin for Prevention of Gram-Negative Bacterial Infections in Patients with Acute Leukemia and Granulocytopenia

Abstract: We evaluated the effect of norfloxacin, 400 mg given orally every 12 hours, on the prevention of bacterial infections in 68 adult patients who had acute leukemia throughout prolonged courses of granulocytopenia (median, 32 days). Gram-negative infections were documented in 13 of the 33 patients receiving placebo, but only in 4 of the 35 patients receiving norfloxacin; no effect on the frequency of gram-positive or fungal infections was noted. Norfloxacin administration resulted in the suppression of gastrointe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
81
1
1

Year Published

1993
1993
2012
2012

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 218 publications
(88 citation statements)
references
References 32 publications
5
81
1
1
Order By: Relevance
“…We have updated our meta-analysis 1 with data from recent trials 2,3 and divided the trials [5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22] according to the type of patient (Fig. 1).…”
Section: Which Patients Should Be Offered Antibiotic Prophylaxis?mentioning
confidence: 99%
“…We have updated our meta-analysis 1 with data from recent trials 2,3 and divided the trials [5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22] according to the type of patient (Fig. 1).…”
Section: Which Patients Should Be Offered Antibiotic Prophylaxis?mentioning
confidence: 99%
“…9,10 The use of prophylactic antibiotics, especially during periods of neutropenia and chronic GVHD, as well as shorter time to engraftment with the use of peripheral stem cells, has decreased the incidence of gram-negative bacteremia from rates of 30-40% in the 1980s to rates of approximately 10-20% more recently. 2,[11][12][13][14] Pseudomonas aeruginosa accounts for a minority of bacteremic episodes in patients undergoing HCT 3,6,15 but is the most common pathogen isolated in bacterial pneumonia occurring before day 100 post-transplant. 4 Owing to antibiotic resistance, it can be difficult to treat 16 and in addition, the colonization of sites such as the lung and gastrointestinal tract may lead to relapse of infection once antibiotics are discontinued.…”
Section: Introductionmentioning
confidence: 99%
“…There maybe other reasons for the very good results of the present study, such as the facts that norfloxacin has a broad antimicrobial spectrum, is poorly absorbed in spite of its high concentration in the gastrointestinal tract, and preserves colonization resistance. Although we didn't have enough data on the surveillance culture and bacteria resistant to norfloxacin, previous reports showed a low prevalence of norfloxacinresistant aerobic bacteria in stool specimens obtained throughout the course of granulocytopenia and indicated that such bacteria appeared to be independent of norfloxacin administration (7,8). Acquired infections in the norfloxacin group were not refractory to the empirical antibiotic treatment, and norfloxacin had no impact on the frequency of gram-positive (including MRSA, Methicillin resistant Staphylococcus aureus) bacterial infections in the present study or in the study of Karp et al (8).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, gram-negative bacterial infections occurred significantly less often in the norfloxacin-treated group (0% to 1 1.4%) (6)(7)(8) compared with the control group (24%, 39%) (7,8) and the group which received non-absorbable antibiotics (16.7%) (6). In the report of Karp et al (8), the mean number of days from starting the chemotherapy to the first febrile episode was longer in the norfloxacin group, and the meannumberof days with a fever during the study period was lower in the norfloxacin group compared with the control group.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation